Consent to minor customary marriages perpetuates abuse towards african girls and women in south africa - Mkandhla, Samantha (Department of Public Law, 2024)
That in terms of South African law, a minor under the age of 18 years, may enter into a valid and legally binding civil or customary marriage if they obtain consent from their parent or guardian, but only if said marriage is found to be “in the best interests of the child”. That, furthermore, this legally permissible minimum age of marriage differs for boys and girls, where the marriageable age of a minor girl has been reduced to 15 years old, while a boy remains at 18 years old. That, while significant in the overall considerations of discrimination, this research did not examine this age difference in detail. That parental consent to minors' marriages applies to minor civil and customary marriages, regulated by the Marriage Act1 and Recognition of Customary Marriages Act2 respectively. That this consent provision also applies to customary marriages is made clear by sections 3(1)(a) and (b) of the latter Act. That this dissertation hypothesises that the provisions that allow a parent or guardian to consent to a marriage entered into by their child, under the respective marriageable ages of 15 and 18 years, have a disproportionately negative impact on black African minor brides who obtain such consent for a customary marriage specifically. That this parental consent usurps section 12(2)(a) of the Children's Act 38 of 2005 of South Africa, which says that a child below the minimum age set by law may not be given out in engagement or marriage. That section 12(2)(b)3 explicitly requires consent to be given out in marriage from a child spouse above the minimum age set for marriage, which is thus between the ages of 15 and 18 years for minor girls, and above 18 years for both minor boys and girls. That this section is important and provides irrefutable legal protection to girl children engaged and/or married between ages 15 and 18 years de jure, but not de facto, especially not for minor girl brides within the context of an African customary marriage. That, additionally, being that this section, enacts the requirement of consent to marry from minors above the minimum age set for marriage, it falls outside the scope of this research in relation to the boy spouse, whose minimum age of marriage remains set at 18 years, because the argument is that marriage below the age of 18 years should not be permissible, with or without the consent of the minor in question. 1 Marriage Act 25 of 1961. 2 Recognition of Customary Marriages Act 120 of 1998. 3 Children's Act 38 of 2005. That this research further demonstrates that in practice, the legislation that empowers a parent or guardian to consent to their minor child's customary marriage simply legalises a child marriage, which is in contravention of South Africa's international law obligations and conflicts with other domestic legislation that made 18 years the minimum permissible age of marriage, for girls and boys. That international and regional instruments include the International Convention on the Rights of the Child, the African Children's Charter, the African Women's Protocol, and the SADC Gender Protocol. That these all seek to advance the rights of children, while judiciously balancing the recognition of other rights such as culture and religion and eliminating harmful practices related to those. That the argument in this dissertation is that while enabling a parent or guardian to consent to the marriage of a child under the minimum age to marry as set by law, could be justified in some contexts, or be interpreted as a measure introduced to protect minors, the customary law setting, debatably renders African girl children particularly vulnerable to the harms associated with child marriage and/ or the interrelated traditional practices, such as ukuthwala. That this dissertation examines the patriarchal foundation of customary law and marriage, questioning whether the parental consent provisions that apply to the customary marriages of girl children, unfairly discriminate against African girls on the grounds of sex and race. That the conclusion reached is that the parental consent provisions do constitute indirect unfair discrimination in terms of section 9(3) of the Constitution of the Republic of South Africa, 1996, on the grounds of race and gender, and that the limitation of the right is not justifiable in terms of its section 36 limitation clause. That the marriage regime researched is limited to heterosexual marriage.